2017
DOI: 10.1007/s00204-017-2118-3
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecenes: immunomodulatory effects, mechanisms, and anti-cancer potential

Abstract: Paradoxically, trichothecenes have both immunosuppressive and immunostimulatory effects. The underlying mechanisms have not been fully explored. Early studies show that dose, exposure timing, and the time at which immune function is assessed influence whether trichothecenes act in an immunosuppressive or immunostimulatory fashion. Recent studies suggest that the immunomodulatory function of trichothecenes is also actively shaped by competing cell-survival and death-signaling pathways. Autophagy may also promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 257 publications
1
56
0
1
Order By: Relevance
“…Studies in Jnk knockout mice revealed that JNK1 promotes the survival of activated T cells during immune responses and that JNK2 modulates CD8 + T cell expansion . Our group recently showed that JNK1/STAT3 is a prosurvival hub that inhibits RAW264.7 cell apoptosis . The JNK1/STAT3 pathway can maintain the normal function of mitochondria and to inhibit T‐2 toxin‐induced cell apoptosis …”
Section: The Yin and Yang Of Jnk1 And Jnk2 In The Regulation Of Cancementioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Jnk knockout mice revealed that JNK1 promotes the survival of activated T cells during immune responses and that JNK2 modulates CD8 + T cell expansion . Our group recently showed that JNK1/STAT3 is a prosurvival hub that inhibits RAW264.7 cell apoptosis . The JNK1/STAT3 pathway can maintain the normal function of mitochondria and to inhibit T‐2 toxin‐induced cell apoptosis …”
Section: The Yin and Yang Of Jnk1 And Jnk2 In The Regulation Of Cancementioning
confidence: 99%
“…68 Our group recently showed that JNK1/STAT3 is a prosurvival hub that inhibits RAW264.7 cell apoptosis. 43,69,70 The JNK1/ STAT3 pathway can maintain the normal function of mitochondria and to inhibit T-2 toxin-induced cell apoptosis. 43 JNK1 and JNK2 regulate the expression of the central transcription initiation factor TATA-binding protein (TBP).…”
Section: Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichothecenes are divided into four types (A-D) depending on their characteristic functional groups [2] (Figure 1), and type A and B are greater food safety concerns because of their high toxicity and frequent occurrence in cereals, feed and food for animals and humans [2,3]. The acute uptake of trichothecenes will cause a wide variety of toxic responses in humans and animals, including gastrointestinal irritation, emesis, diarrhea, hemorrhage, leukopenia, immunosuppression and mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when mice were pre-treated with high dose of T-2 (4 mg/kg bw) and thereafter vaccinated with sheep red blood cells (RBCs), PA increased. But when the toxin was administered after sensitisation, significantly suppressed phagocytosis of sheep RBC was observed (Wu et al 2017).…”
Section: Immune Responsementioning
confidence: 99%